State capacity and regime resilience in Putin's Russia. Issue 1 (January 2018) - White, David
Vladimir Putin's state-building project, which has included a 'war on the oligarchs', the reining in of regional power, the co-optation or marginalization of civil society and political opposition, and the establishment of a 'power vertical', has not been based on state strengthening but has had much more to do with regime consolidation. It is argued that, in the Russian case, the building of state capacity may not be a crucial factor in determining the medium or even the long-term survival of the authoritarian system. Although Russia has relatively weak state capacity, the Putin regime has remained stable. The regime's resilience is built on the distribution of rents among political and economic elites, the provision of social welfare, the coercion or co-opting of civil society and political opposition, and the mobilization of public support through the provision of economic benefits and national-patriotic appeal.